Efficacy of Wheat Insecticide Seed Treatments on Bird Cherry-Oat Aphids - Wastler, Justin; Davis, Holly; Whitworth, Jeff (My University, 2018)
Bird Cherry-Oat Aphids, Rhopalosiphumpadi (Linnaeus), (BCOA) are a major agricultural pest for wheat due to their ability to transferBarley Yellow Dwarf Virus (BYDV), which can stunt growth when introduced to seedlings (Wegulo, 2013). These aphids, which will remain infective throughout their lives, are capable of asexual reproduction thus populations can grow exponentially and BYDV can spread rapidly throughout a field (Whitworth & Ahmad, 2008) ”). However, seed treatments, the application of pesticides to “seeds or vegetative propagation materials,” are an effective way to defend crops from pests like BCOA during their most vulnerable life cycle stages. (Paulsrudet al, 2001). Chemical companies are always seeking to develop ever more effective treatments. This research compared the effectiveness of an experimental treatment to that of Poncho®, a proven aphid pesticide. The results showed that the BCOA populations on the plants treated with the experimental pesticide did not decline. In fact, they increased at a faster rate than the untreated control. This indicates that the experimental treatment is not suitable for the control of aphids.
Keywords: Fall 2018